2019
DOI: 10.2147/dmso.s191759
|View full text |Cite
|
Sign up to set email alerts
|

<p>Interaction between dietary patterns and <em>TCF7L2</em> polymorphisms on type 2 diabetes mellitus among Uyghur adults in Xinjiang Province, China</p>

Abstract: Purpose This study aimed to characterize dietary patterns in the Uyghur population and examined the relationship between dietary pattern, TCF7L2 single-nucleotide polymorphisms (SNPs), and the risk of type 2 diabetes mellitus (T2DM). Patients and methods Dietary patterns were defined using factor analysis, and associations between dietary patterns were evaluated using multivariate logistic regression analyses. Genotyping of seven SNPs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Factor loading |≥0.4| of food products was considered as making a significant contribution to the factor structure. As a rule, factor loading with a value of |≥0.2| was used; however, depending on the data obtained, higher values were also used [29][30][31][32]. DPs were named according to the variables loaded on a retained component.…”
Section: Definition Of Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor loading |≥0.4| of food products was considered as making a significant contribution to the factor structure. As a rule, factor loading with a value of |≥0.2| was used; however, depending on the data obtained, higher values were also used [29][30][31][32]. DPs were named according to the variables loaded on a retained component.…”
Section: Definition Of Dietary Patternsmentioning
confidence: 99%
“…Participants were divided into four groups (quartiles, Q) for each DP. Then, in the course of evaluating the influence of socio-demographic and regional characteristics, a comparison was made of individuals relating to the highest Q4 quartile to all others (i.e., Q1, Q2, and Q3), as done previously in [27,28,30,32].…”
Section: Definition Of Dietary Patternsmentioning
confidence: 99%
“…Although it is suggested that the TCF7L2 gene is involved in nearly a fifth of all T2DM cases [7], T2DM should not be considered only a genetic disorder, since most cases result from polygenic and multifactorial, especially gene-environmental interactions [4,13]. In our previous study, we noted lower glucose utilization [12] and an altered lipid metabolism [14] in healthy subjects carrying the high-risk CC genotype, rs7901695, of the TCF7L2 gene after consuming high-carbohydrate meals.…”
Section: Introductionmentioning
confidence: 69%
“…T2DM patients are at higher risk of cardiovascular morbidity and mortality [2]; therefore, more effective prophylaxis and treatments are urgently required. Large-scale genome-wide association studies (GWAS) have revealed that one of the greatest genetic risk factors for T2DM is conferred by the TCF7L2 (transcription factor-7-like 2) gene [3,4]. The increased risk of T2DM conferred by genetic variations in TCF7L2 involves various mechanisms, including the modulation of the enteroinsular axis and enhanced expression of the gene in islets, affecting the function of β-cells and impairing insulin secretion [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, the Diabetes Prevention Program and the Diabetes Prevention Study reported that lifestyle intervention reduces diabetic risk among individuals with genetic susceptibility of TCF7L2 risk genotypes [ 7 , 8 ]. Followed by this investigation, current literature suggests associations of this gene with the risk of type 2 diabetes, obesity, and MetS while considering the modulating effects of some dietary determinants, such as whole-grains [ 9 ], glycemic index and glycemic load [ 10 ], dietary fiber [ 11 ], low fat and high carbohydrate diet [ 12 ], dietary saturated fatty acids (SFA) [ 13 ], western dietary pattern [ 14 ], and prudent dietary pattern [ 15 ]. However, to the best of our knowledge, the interaction between nut consumption and polymorphisms of this gene has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%